2013
DOI: 10.1016/j.marenvres.2013.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Isolation By Distance (IBD) signals in the deep-water rose shrimp Parapenaeus longirostris (Lucas, 1846) (Decapoda, Panaeidae) in the Mediterranean Sea

Abstract: The identification of boundaries of genetic demes is one of the major goals for fishery management, and few Mediterranean commercial species have not been studied from a genetic point of view yet. The deep-water rose shrimp Parapenaeus longirostris (Lucas, 1846) is one of the most important components of commercial landings in Mediterranean, its fishery aspects have received much attention, regrettably without any concern for the genetic architecture of its populations. The population structure in the central … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 63 publications
(70 reference statements)
2
5
0
Order By: Relevance
“…These results are supported by genetic data showing minor differences for individuals from the West and East sectors of the SoS, thus confirming our connectivity results, and the presence of a gradual discrepancy along a west-east axis coherent with an ‘Isolation By Distance’ model, within the Mediterranean Sea 19 . It would be however advisable to extend the genetic analysis to African region to have a refined knowledge on the genetic pattern of DPS in the whole SoS domain, which would be clearly relevant for the management of the stock since its exploitation is shared between EU (Italy, Malta) and north African countries (Tunisia, Libya and Egypt).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These results are supported by genetic data showing minor differences for individuals from the West and East sectors of the SoS, thus confirming our connectivity results, and the presence of a gradual discrepancy along a west-east axis coherent with an ‘Isolation By Distance’ model, within the Mediterranean Sea 19 . It would be however advisable to extend the genetic analysis to African region to have a refined knowledge on the genetic pattern of DPS in the whole SoS domain, which would be clearly relevant for the management of the stock since its exploitation is shared between EU (Italy, Malta) and north African countries (Tunisia, Libya and Egypt).…”
Section: Discussionsupporting
confidence: 89%
“…Results obtained on the northern side of the area therefore suggested that contiguous spawning and nursery areas on Adventure Bank and Maltese Plateau are connected through larval drifting by the Atlantic Ionian Stream that is flowing in surface waters 28,37 . In 2013 a first study 19 on the genetic structure of DPS in the central and eastern Mediterranean Sea identified some minor differences between samples from the western and eastern side of the SoS, and a general mixing in the DPS inhabiting the Northern part of the SoS that is still considered as a single stock 38 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S4) and suggests that the Strait of Sicily is a more permeable barrier than the Strait of Gibraltar for A. antennatus , given that the former is much deeper (360–430 m) and wider (130 km) than the latter 21 . IBD signals along the WM–EM axis also have been detected in the decapod P. longirostris 42 . Thus, the EM stock of A. antennatus might be affected by adaptations to the Eastern Mediterranean Basin due to differences in environmental conditions from the Western Mediterranean Basin 21 .…”
Section: Discussionmentioning
confidence: 86%
“…Sediments are integrated components of aquatic ecosystems, and have been recognized as sinks of heavy metals [ [1] , [2] , [3] , [4] , [5] , [6] , [7] ]. Heavy metal concentration data are commonly applied in monitoring and assessing the degree of contamination of aquatic environments using sediment quality indices [ 2 , [8] , [9] , [10] , [11] , [12] , [13] , [14] ].…”
Section: Methods Detailsmentioning
confidence: 99%